2009
DOI: 10.2340/16501977-0374
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pulsed electromagnetic field therapy in the management of osteoarthritis of the knee: A meta-analysis of randomized controlled trials

Abstract: Pulsed electromagnetic fields improve clinical scores and function in patients with osteoarthritis of the knee and should be considered as adjuvant therapies in their management. There is still equipoise of evidence for an effect on pain in the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 15 publications
2
57
0
2
Order By: Relevance
“…Since approval by the US FDA, it has been applied to diverse treatments. Recent clinical researches on pain have mainly focused on knee osteoarthritis [9][10][11], fibromyalgia [13], diabetic neuropathic pain [14] and posto- Data are mean ± SD; P-value, compared with Sham group; *p < 0.05 (compared with Baseline); **p < 0.01 (compared with Baseline); ***p < 0.001 (compared with Baseline), †, Fisher's Exact Test; ‡, Mann-Whitney U-test; PEMF, pulsed electromagnetic field; VASB, Visual Analogue Scale for bothersomeness; VASP, Visual Analogue Scale for pain; ODI, Oswestry Disability Index; SF-36, 36-Item Short Form Health Survey Instrument; EQ-5D, EuroQol-5Dimension; BDI, Beck's Depression Inventory; RMDQ, Roland-Morris Disability Questionnaire perative pain [15], rheumatoid arthritis [12] and multiple sclerosis [18] etc. The principle of pulsated extracorporeal pulsed electromagnetic therapy is the induction of eddy currents in the body if portion of the body is within the range of formation of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since approval by the US FDA, it has been applied to diverse treatments. Recent clinical researches on pain have mainly focused on knee osteoarthritis [9][10][11], fibromyalgia [13], diabetic neuropathic pain [14] and posto- Data are mean ± SD; P-value, compared with Sham group; *p < 0.05 (compared with Baseline); **p < 0.01 (compared with Baseline); ***p < 0.001 (compared with Baseline), †, Fisher's Exact Test; ‡, Mann-Whitney U-test; PEMF, pulsed electromagnetic field; VASB, Visual Analogue Scale for bothersomeness; VASP, Visual Analogue Scale for pain; ODI, Oswestry Disability Index; SF-36, 36-Item Short Form Health Survey Instrument; EQ-5D, EuroQol-5Dimension; BDI, Beck's Depression Inventory; RMDQ, Roland-Morris Disability Questionnaire perative pain [15], rheumatoid arthritis [12] and multiple sclerosis [18] etc. The principle of pulsated extracorporeal pulsed electromagnetic therapy is the induction of eddy currents in the body if portion of the body is within the range of formation of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…PEMF therapy is effective for bone fractures [7,8], arthritis [9][10][11], fibromyalgia [12,13], neuropathic pain [14], postoperative pain [15], musculoskelectal pain [16,17] and multiple sclerosis [18]. But there are few clinical trials on lumbago [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Mollan et al concluded that the application of PEMF did not influence long-bone fracture healing [14]. Varken et al reported that applying PEMF to knee osteoarthritis did not improve pain control or joint stiffness [15].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the daily living activities and functional scores improved significantly (LOE Ia). [42] It was shown that pulsed electromagnetic field therapy was not superior to conventional physical therapy (LOE Ib). [43] Pulsed electromagnetic field treatment did not exist in guidelines published before the 2010 update of the OARSI recommendations.…”
Section: Electrotherapeutic Agents Such As Tens Interferential Currementioning
confidence: 99%